Factors Influencing the Use of Delivery Services: A Study of Service Quality, Timeliness, and Social Media - Heri Prasetyo; Sudarwati Sudarwati; Eko Giyartiningrum (Universitas KH. Abdul Chalim Mojokerto, 2024)
The purpose of this study was to see the effect of service quality (X1), timeliness of delivery (X2), and social media promotion (X3) on the decision to use goods delivery services (Y) at PT. Yogyakarta Logistics Achievement Forum. Data was collected by distributing questionnaires to 75 customers. The sampling technique used was purposive sampling. The method of analysis is the multiple linear regression test, simultaneous significance test (F test), partial significance test (t-test), and coefficient of determination test (R2). It was found that X1, X2, and X3 partially and simultaneously have a significant influence on the decision to use services. The coefficient of determination (R2) shows the quality of service, timeliness of delivery, and promotion of social media which can be explained by the service use decision variable of 79.3%. The coefficient of the variable that most influences the decision to use the service is the variable on the time of delivery.